2022
DOI: 10.9767/bcrec.17.2.13482.240-249
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Degradation of Malachite Green by Layered Double Hydroxide Based Composites

Abstract: Studies of LDH materials to be applied as photocatalyst for dye pollutant degradation have been developed. These interesting efforts are inseparable from the investigation of degradation performance and competitive synthetic methods. Composites based on Zn/Al and Mg/Al layered double hydroxides (LDHs) with ZnO and TiO2 were prepared by coprecipitation-impregnation method following by calcination at 300 °C to forms Zn/Al-ZnO, Mg/Al-ZnO, Zn/Al-TiO2, and Mg/Al-TiO2. Composites were characterized by XRD, FTIR, SEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…It can be seen in the gure that the heavier the catalyst used, the better the photodegradation tendency. The decrease in the photodegradation performance of the Zn/Al-ZnO catalyst at 0.1 g according to Elhalil et al (2018) and Yuliasari et al (2022b) could be due to light being more di cult to penetrate into the media. LDH materials can be modi ed with metal oxides to form composites that have better structural strength (Djeda et al, 2020;Yuliasari et al, 2022a).…”
Section: E Ect Of Photodegradation Conditionsmentioning
confidence: 88%
“…It can be seen in the gure that the heavier the catalyst used, the better the photodegradation tendency. The decrease in the photodegradation performance of the Zn/Al-ZnO catalyst at 0.1 g according to Elhalil et al (2018) and Yuliasari et al (2022b) could be due to light being more di cult to penetrate into the media. LDH materials can be modi ed with metal oxides to form composites that have better structural strength (Djeda et al, 2020;Yuliasari et al, 2022a).…”
Section: E Ect Of Photodegradation Conditionsmentioning
confidence: 88%
“…Figure 5 shows the UV-DRS pristine and composite's LDH spectrum energies. According to Wijaya et al (2021) , the abscissa value of the NiAl-LDH is hv or energy band gap, curve coordinates are valued (𝛼hv) 2 , where 𝛼 is the absorptivity coefficient, h is the plank constant and v is the light frequency (Yuliasari et al, 2022) .…”
Section: Ldh Pristine and Ldh Composite Characterizationmentioning
confidence: 99%
“…Figure 8 shows the band gap energies of LDH pristine and LDH composite. According to Yuliasari et al [18], LDH catalyst has a direct transition type, so that the curve coordinates are valued (αhv) 2 , where α is the absorptivity coefficient, h is the plank constant, and v is the light frequency [43]. This study demonstrated that the photocatalytic performance of LDH materials depends on interlayer anion, metal combination, and cation ratio [44].…”
Section: Kinetics Of Degradationmentioning
confidence: 69%
“…Recently, the application of LDH as a photocatalyst that degrades organic pollutants has been synthesized with various compounds. It is adopted strategies to decorate LDH-based materials to enhance efficiency performance in any application [15], including doping with noble metal [16], forming heterostructure with metal oxide [17], etc., Yulisari et al [18] reported that metal oxide (ZnO and TiO2) modified LDH (Zn/Mg-Al) was synthesized as a catalyst for degrading malachite green, which is informed that LDH composite has better performance than LDH pristine. Gholami et al [19] combining biochar with Zn-Co-LDH was composited for photocatalytic removal of gemifloxacin antibiotic.…”
Section: Introductionmentioning
confidence: 99%